2015
DOI: 10.1073/pnas.1400555112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the effect of the novel BK channel opener GoSlo: Involvement of the S4/S5 linker and the S6 segment

Abstract: GoSlo-SR-5-6 is a novel large-conductance Ca 2+ -activated K + (BK) channel agonist that shifts the activation V 1/2 of these channels in excess of −100 mV when applied at a concentration of 10 μM. Although the structure-activity relationship of this family of molecules has been established, little is known about how they open BK channels. To help address this, we used a combination of electrophysiology, mutagenesis, and mathematical modeling to investigate the molecular mechanisms underlying the effect of GoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…This supports the idea that they relaxed Gracilis muscle arteries by activating both BK and K v 7 channels. This dual action of GoSlo‐SR compounds on BK and K v 7.4/K v 7.5 channels is further supported by the findings made on single cells expressing these channels, that is, (a) our findings reported in the present study demonstrating that GoSlo‐SR compounds produce a large stimulation of native BK currents and K v 7.4 and K v 7.5 channels and (b) previously published findings showing that GoSlo‐SR compounds activate expressed as well as native BK channels (Hannigan et al, ; Kshatri et al, ; Large et al, ; Roy et al, ; Roy et al, ; Webb et al, ). Incidentally, the BK channel opener NS11021 has been shown to stimulate expressed K v 7.4 channels (Bentzen et al, ), and BMS204352 activates both BK and K v 7 channels (Schroder, Strobaek, Olesen, & Christophersen, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This supports the idea that they relaxed Gracilis muscle arteries by activating both BK and K v 7 channels. This dual action of GoSlo‐SR compounds on BK and K v 7.4/K v 7.5 channels is further supported by the findings made on single cells expressing these channels, that is, (a) our findings reported in the present study demonstrating that GoSlo‐SR compounds produce a large stimulation of native BK currents and K v 7.4 and K v 7.5 channels and (b) previously published findings showing that GoSlo‐SR compounds activate expressed as well as native BK channels (Hannigan et al, ; Kshatri et al, ; Large et al, ; Roy et al, ; Roy et al, ; Webb et al, ). Incidentally, the BK channel opener NS11021 has been shown to stimulate expressed K v 7.4 channels (Bentzen et al, ), and BMS204352 activates both BK and K v 7 channels (Schroder, Strobaek, Olesen, & Christophersen, ).…”
Section: Discussionsupporting
confidence: 91%
“…These data suggested that GoSlo‐SR compounds either interfered with the binding of BK channel blockers or that they activated other K + channels. The former explanation appears unlikely, given that the effects of GoSlo‐SR compounds have been shown to be blocked with IBTX and penitrem A in tissue strips (Hannigan et al, ; Large et al, ) and in single cells (Webb et al, ) and that in our study IBTX inhibited the effect of GoSlo‐SR compounds in the tail artery and regained a blocking effect against GoSlo‐SR compounds in the presence of the K v 7 channel inhibitor XE991 (for more details, see below).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…where L 0 is the value of L at 0 mV, Z L is the partial charge associated with the channel opening (C → O), and V, K, and T are same as above. The logarithmic slope of the P O -V curve relationship gives the mean activation displacement Qa, which estimates the total charge movement upon channel opening (Sigg and Bezanilla, 1997;Webb et al, 2015). This is defined as (Eq.…”
Section: Electrophysiologymentioning
confidence: 99%